Investigating causes of the high prevalence of sexually transmitted infections in Du Noon - Azhaar B.F. Dookhith; Adil Razack; Abdul-Aziez Isaacs (South African Family Practice)
Background: In South Africa, sexually transmitted infections (STIs) represent a significant public health issue. Sexually transmitted infections contribute significantly to the burden of disease in South Africa and are recognised as one of the main causes of the human immunodeficiency virus (HIV) epidemic. The aim of this study was to investigate the potential causes of the high prevalence of STIs in the Du Noon population.